Adoption of Children and Its Limits in Interacting with Adoptive Parents - Hakim, Abdul (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2024)
Child adoption is governed by both Islamic jurisprudence (fiqh) and positive law, but these regulations are often overlooked by many adopting parties, leading to violations of both religious and legal principles. The objective of this article is to analyze the adoptive parent-child relationship in a family from a fiqh perspective and evaluate the implications of this relationship on their daily interactions.The research conducted in this article employs a qualitative literature review method with a descriptive and comparative approach. Data sources include classical fiqh texts, current legal statutes, and recent scholarly articles. Fundamentally, fiqh and positive law both prohibit attributing lineage from adopted children to their adoptive parents. As a result, these prohibitions create boundaries that affect the interactions between adoptive parents and adopted children in their daily lives. Unfortunately, the disregard for these boundaries often leads both parties to engage in actions that go against fiqh and positive law.